THE UNEMPLOYMENT EVO LUTION IN ROMANIA - Mihaela, Savu; Mihaela, Bursugiu (Strategii Manageriale)
Unemployment represents a phenomenon frequently met in the economy of any state. This paper presents the unemployment evolution in Romania in order to observe its evolution and the category of people affected by unemployment, from the sex point of view. The statement that women are more affected by unemployment in our country, is not supported by the presented figures. The interval chosen to analyse the unemployment also includes a period in which the the Romanian economy was affected by depression, so that one could observe that the unemployment rate increased.